Development of a web based virtual forest environment to increase threatened plant species awareness - Norul Maslissa Ahmad; Nazlena Mohamad Ali; Ang, Mei Choo (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper reports on the development of a web based virtual forest environment to raise the awareness of threatened plant species in particular for the family of Dipterocarpaceae. Tropical forests in Malaysia consists of unique ecosystems which are home to flora and fauna including the threatened plant species that are listed in the Red List by the Forest Research Institute of Malaysia. However, the lack of awareness on the threatened plant species somehow can jeopardise on the effort on conservation of the forest. A web based utilizing virtual environment were developed that focussed on threatened plant species. User experiments were conducted to evaluate the user acceptance on the developed application. 30 participants were divided into two groups, brochures and web version. Results showed that participants who completed the experiments with web based virtual environment increased their level of awareness as compared to the usage of conventional brochures on threatened plant species.